2015
DOI: 10.1371/journal.pone.0136119
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners Views of Implementing a Stratified Treatment Approach for Low Back Pain in Germany: A Qualitative Study

Abstract: Background and ObjectiveThe STarT Back stratified primary care approach has demonstrated clinical and cost effectiveness in the UK, and is commonly used by General Practitioners (GPs). However, it remains unknown how this approach could be implemented into the German healthcare system. The aim of this study was therefore to explore the views and perceptions of German GPs in respect to using a stratified primary care for low back pain (LBP).MethodsA 90-minute think-tank workshop was conducted with 14 male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(92 citation statements)
references
References 33 publications
4
87
0
1
Order By: Relevance
“…Findings reported here show both similarities and differences with other qualitative studies into stratified care for MSK pain [32][33][34], including our own earlier paper [19]. In our 2016 paper, some similar barriers were anticipated to those found here, such as difficulty integrating the tool within the consultation time-frame; disruption to the flow of the consultation; and the lack of availability of some matched treatment options.…”
Section: Motivationsupporting
confidence: 81%
See 1 more Smart Citation
“…Findings reported here show both similarities and differences with other qualitative studies into stratified care for MSK pain [32][33][34], including our own earlier paper [19]. In our 2016 paper, some similar barriers were anticipated to those found here, such as difficulty integrating the tool within the consultation time-frame; disruption to the flow of the consultation; and the lack of availability of some matched treatment options.…”
Section: Motivationsupporting
confidence: 81%
“…In exploring GPs' views on stratified care for LBP in Germany, Karstens et al [33] reported the potential for stratified care to negatively impact upon the therapeutic relationship through undermining GP-patient rapport, a similar finding in our 2016 paper. This partly supports our present finding that patients perceived the closed nature of tool items as hindering the discussion of certain issues, which may indicate some negative impacts on GP-patient communication.…”
Section: Motivationsupporting
confidence: 74%
“…has generated great interest in developed countries, providing new hope that meaningful improvements in primary care for LBP are within reach. [14][15][16][17][18][19] Prior to widespread implementation, it would be valuable to know if the STarT Back strategy can be successfully translated to other settings. To determine if the STarT Back risk stratification strategy would succeed in the USA, we conducted the Matching Appropriate Treatments to Consumer Healthcare needs (MATCH) cluster randomized trial.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Research findings in primary care settings have similarly identified the need to accommodate diverse practitioner preferences and clinical environments 37 44 and also recommended enabling electronic, phone application and computer-embedded platforms for use. 44 Finally, the desire for guidance on communicating the CPR's results to patients may reduce fear of unintended consequences from CPR use. 18 Provision of a framework that assists communicating unfavourable news to patients 45 and transitions medical information into lay language 46 have been advocated in the past.…”
Section: Discussionmentioning
confidence: 99%